Oracle data warehouse tuning for 10g - Powell, Gavin (Burlingham, MA : Elsevier Digital Press, 2005)
This book should satisfy those who want a different perspective than the official Oracle documentation. It will cover all important aspects of a data warehouse while giving the necessary examples to make the reading a lively experience. - Tim Donar, Author and Systems Architect for Enterprise Data Warehouses Tuning a data warehouse database focuses on large transactions, mostly requiring what is known as throughput. Throughput is the passing of large amounts of information through a server, network and Internet environment, backwards and forwards, constantly! The ultimate objective of a data warehouse is the production of meaningful and useful reporting, from historical and archived data. The trick is to make the reports print within an acceptable time frame. A data model contains tables and relationships between tables. Tuning a data model involves Normalization and Denormalization. Different approaches are required depending on the application, such as OLTP or a Data Warehouse. Inappropriate database design can make SQL code impossible to tune. Poor data modeling can have a most profound effect on database performance since all SQL code is constructed from the data model. * Takes users beyond basics to critical issues in running most efficient data warehouse applications * Illustrates how to keep data going in and out in the most productive way possible * Focus is placed on Data Warehouse performance tuning.
Introduction to Data Warehousing; Data Warehouse Data Modeling; Making Hardware and I/O Perform in a Data Warehouse; Data Warehouse Physical Architecture; Effective Data Warehouse Indexing; Constraints and Integrity in Data Warehouses; Using Partitioning and Tuning Parallel Processing; Materialized Views and Query Rewrites; Oracle Dimension Objects; Data Loading: Extraction and Transportation; Data Loading: Loading and Transformation; SQL Aggregation Using GROUP BY Clause Extensions.
Includes bibliographical references (p. 449-450) and index.
Keywords: Data warehousing; Oracle (Computer file); Electronic books